2016
DOI: 10.1093/infdis/jiw090
|View full text |Cite
|
Sign up to set email alerts
|

Statin Concentrations Below the Minimum Inhibitory Concentration Attenuate the Virulence ofRhizopus oryzae

Abstract: Exposure of R. oryzae to statins at concentrations below their MICs decreased virulence both in vitro and in vivo. Further investigation is warranted into the use of statins as adjunctive therapy in mucormycosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“…63 Another class of drugs with possible antifungal properties are the statins. A previous study 65 found a synergistic antifungal effect of lovastatin with azoles in vitro, whereas a recent experimental study 66 found that use of statins significantly affected various biologic functions of R oryzae and affected its virulence. Because statins are frequently prescribed agents, the clinical result of their use in combination with antifungal agents should be sought.…”
Section: Implications and Future Directionsmentioning
confidence: 95%
“…63 Another class of drugs with possible antifungal properties are the statins. A previous study 65 found a synergistic antifungal effect of lovastatin with azoles in vitro, whereas a recent experimental study 66 found that use of statins significantly affected various biologic functions of R oryzae and affected its virulence. Because statins are frequently prescribed agents, the clinical result of their use in combination with antifungal agents should be sought.…”
Section: Implications and Future Directionsmentioning
confidence: 95%
“…Granulocyte transfusions have also been tested with unclear success but with some risk for inflammatory lung injury [ 110 ]. Statins have shown in vitro and in vivo activity against Rhizopus spp., but reliable clinical data are lacking [ 111 , 112 ]. In a recent case report, an immunosuppressed, trauma patient with intractable mucormycosis was successfully treated with combination of interferon-γ and nivolumab [ 113 ], a monoclonal antibody that decreases programmed death-1 (PD-1) expression on T-cells.…”
Section: Treatmentmentioning
confidence: 99%
“…After a lag time of 3 to 4 days, mice were immunocompromised with cortisone acetate combined to cyclophosphamide. This combination was commonly used in mucormycosis animal models (15,(31)(32)(33)(34)(35). Corticosteroids are used to suppress pulmonary alveolar macrophage function.…”
Section: Methodsmentioning
confidence: 99%
“…Cortisone acetate (Sigma) was dissolved in PBS containing 0.01% Tween 20 (Sigma) to obtain a 50 mg/ml solution, and cyclophosphamide (Sigma) was dissolved in PBS (40 mg/ml). Both drugs were administered intraperitoneally (IP) every 5 days at 500 mg/kg and 200 mg/kg, respectively (15,(31)(32)(33)(34)(35). All immunosuppressive drugs were prepared at the day of use.…”
Section: Methodsmentioning
confidence: 99%